Annual Plan 1966-67 - Planning Commission (Planning Commission, 1966)
The Annual Plan for 1966-67 presented in this document, though formulated in advance of the Draft Outline for the Fourth Plan, has to be viewed with the broad framework of the Five-Year Plan set out in the Memorandum submitted to the National Development Council in September, 1965. It is inevitable that the Plan for 1966-67 takes into account the existing strains in the economy, arising from the many unforeseen events of the Third Plan period. At the same time, it must seek to keep in accord with the objectives and strategy which underly the developmental efforts in the Fourth Plan period. As will be explained later, it has not, been easy to strike a balance between these considerations of offsetting immediate strains and of ensuring an adequate start towards the realisation of our longer-term objectives.
Government of India Planning Commission
Government of India Planning Commission